Investigating electromagnetic properties of brain tissue using 7 T MRI - Kleban, Elena (2018)
Magnetic Resonance Imaging allows electromagnetic properties of the brain to be measured in vivo, providing new markers of structure at a microscopic level. Evaluation of the local complex signal evolution observed using a multi-echo gradient-echo (MEGE) sequence can allow the electromagnetic and relaxivity properties of individual tissue compartments to be accessed. The phase evolution carries valuable information about the different compartments, but is dominated by non-local, large-length-scale field variations which present the main challenge in processing complex MEGE data. In this work 2-compartment and 3-pool models are used to describe signal evolution from a mixed tissue and venous compartment and from white matter, respectively. A new method for removing the effects of non-local field variations without corrupting local non-mono-exponential phase evolution is proposed. The 2-compartment model of venous blood complex signal has been used to access the vascular dependence on orientation and oxygenation levels, and has been validated against existing methods on large distinguishable veins. A phantom consisting of capillary tubes filled with ferritin solution immersed in a water bath has been used to validate the 2-compartment model and the estimated frequency offsets between the ferritin and water compartments at multiple orientations to B⃗0 shown to agree with predictions of theory.